1979
DOI: 10.1097/00006842-197903000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Monoamine Oxidase Activity Correlates with Social Affiliative and Agonistic Behaviors in Normal Rhesus Monkeys

Abstract: After a 4-mo study period, quantitative measures of stable behavioral traits in individual rhesus monkeys correlated significantly with platelet monoamine oxidase (MAO) activity. In particular, behavioral items reflecting social activity and social contact, both agonistic and affiliative, were inversely correlated with enzyme activity. Time spent alone was positively correlated. Since platelet MAO activity is generally stable and predominantly controlled by genetic factors, it might serve as a "genetic marker"… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

1980
1980
2012
2012

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…The clinical correlates of high platelet M A 0 activity (anxiety, 13; depression, secondary to anxiety, 9; schizophrenia-related depression, 10; and paranoia, 14) seem consistent with the personality correlates in the present study. In line with these findings are results on monkeys with high platelet M A 0 activity who showed a strong tendency to social isolation (51). Of interest are also recent neuropsychological findings from our group (52), suggesting a reversal of cerebral asymmetries in high M A 0 subjects.…”
Section: Discussionsupporting
confidence: 85%
“…The clinical correlates of high platelet M A 0 activity (anxiety, 13; depression, secondary to anxiety, 9; schizophrenia-related depression, 10; and paranoia, 14) seem consistent with the personality correlates in the present study. In line with these findings are results on monkeys with high platelet M A 0 activity who showed a strong tendency to social isolation (51). Of interest are also recent neuropsychological findings from our group (52), suggesting a reversal of cerebral asymmetries in high M A 0 subjects.…”
Section: Discussionsupporting
confidence: 85%
“…MAO-B is under complete genetic determination and a gene has been found underlying the enzyme. Comparative correlational results from an MAO study of monkeys observed in a colony living in a natural island environment parallel many of the human personality and behavioral results (Redmond, Murphy, & Baulu, 1979). Low MAO monkeys of both sexes were more active and social and spent more time in play than high MAO monkeys.…”
Section: Monoamine Oxidasementioning
confidence: 60%
“…8,9 In studies on non-human primates, associations between trbc MAO and behavior were reported, which, in essence, confirmed the findings in humans. 10 Those early studies on rhesus monkeys have recently been nicely confirmed and considerably extended. 11 Other support for a connection between the enzyme and CNS function stems from the report by Sostek et al 12 that trbc MAO activity is related to the behavior in new-born babies such as screaming and motor activity as well as their consolability.…”
Section: Thrombocyte Monoamine Oxidase As a Biological Markermentioning
confidence: 87%